Tradisi Pitung di Kalangan Warga Nahdliyin dalam Penentuan Hari Pernikahan di Desa Wonokerto: Analisis Fenomenologi Alfred Schutz dan Maqāṣid al-Sharī‘ah - M. Syaiful Huda (Lakpesdam PCNU Kota Salatiga, 2023)
The pitung tradition (weton calculation/determining an auspicious day) for selecting a wedding date is still practiced among Nahdliyin residents in Wonokerto Village, Bancak Subdistrict, Semarang Regency, although some perceive it as a practice that potentially deviates from the boundaries of Islamic creed (aqidah) and law (shari‘ah). Against this backdrop, the study formulates three research foci: (1) the empirical reality of pitung practices in determining wedding dates in Wonokerto Village; (2) the motives underlying community actions based on Alfred Schutz’s phenomenology (because-motives and in-order-to motives); and (3) the orientation of the tradition as examined through the paradigm of Maqāṣid al-Sharī‘ah. The research employs a qualitative approach using a juridical–sociological method (fieldwork) through interviews with three tradition practitioners, complemented by triangulation, and analyzed using Miles and Huberman’s interactive model (data collection, reduction, display, and verification). The findings show that pitung is understood by the community as an effort grounded in local knowledge to seek safety and blessings for marriage; phenomenologically, the practice is driven by because-motives such as attachment to tradition, respect for ancestors, and belief in the value of safety, as well as in-order-to motives oriented toward building a sakinah, mawaddah wa rahmah family; meanwhile, within the framework of Maqāṣid al-Sharī‘ah, its orientation is considered consistent with maslahah (public benefit) particularly the protection of lineage and family resilience because the tradition is positioned as a means (wasilah) of endeavor without negating the belief that the final outcome ultimately rests with Allah SWT.